2018
DOI: 10.3748/wjg.v24.i21.2291
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-enriched diet helps to control symptoms and improves esophageal motility in patients with non-erosive gastroesophageal reflux disease

Abstract: AIMTo investigate the effect of dietary fiber on symptoms and esophageal function testing parameters in non-erosive gastroesophageal reflux disease (GERD) (NERD) patients.METHODSThirty-six NERD patients with low (< 20 g/d) dietary fiber intake were enrolled in the study. They were examined with the use of symptom questionnaire (GERD-Q), high-resolution esophageal manometry, 24-h esophageal pH-impedance examinations, and food frequency questionnaire before and after 10 d of usual diet supplemented by psyllium 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 40 publications
1
44
0
3
Order By: Relevance
“…The effect of anti-reflux diet with or without additional minimally invasive endoscopic techniques needs assessment. 25 Patients psychological comorbidities in GER 10 need to be assessed separately as anxiety and depression won't respond to conventional anti-reflux treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of anti-reflux diet with or without additional minimally invasive endoscopic techniques needs assessment. 25 Patients psychological comorbidities in GER 10 need to be assessed separately as anxiety and depression won't respond to conventional anti-reflux treatment.…”
Section: Discussionmentioning
confidence: 99%
“…92 Dietary intervention benefits esophageal symptoms mainly by facilitating swallows, but may also impact esophageal contractility. 116 With the hypothesis that dietary fiber binds nitric oxide (NO) contained in food, and could reduce the inhibitory effects of NO in the esophagus, psyllium (15 g/d) was reported to decrease esophageal symptoms and increase LES resting pressure in patients with GERD. 116 However, effects on esophageal contractility were not reported in this open-label study.…”
Section: Manag Ementmentioning
confidence: 99%
“…116 With the hypothesis that dietary fiber binds nitric oxide (NO) contained in food, and could reduce the inhibitory effects of NO in the esophagus, psyllium (15 g/d) was reported to decrease esophageal symptoms and increase LES resting pressure in patients with GERD. 116 However, effects on esophageal contractility were not reported in this open-label study. Transcranial direct current stimulation of the brain has been reported to improve esophageal contractility in NERD and functional heartburn in a randomized double-blind sham-controlled study.…”
Section: Manag Ementmentioning
confidence: 99%
“…Precise evaluation of the data provided showed that most of the patients in the study had signs of small intestinal bacterial overgrowth according to the hydrogen breath test, which could have impacted the study results. Our own data suggest the contrary: soluble fibre (psyllium) leads to a significant improvement of symptoms in patients with non‐erosive GERD, rather than exacerbate them. Moreover, addition of soluble fibre leads to a decrease in the number of gastro‐oesophageal refluxes per 24‐hour oesophageal pH‐impedance monitoring and an increase in minimal lower oesophageal sphincter resting pressure.…”
mentioning
confidence: 69%